Genes involucrados en la Amelogénesis Imperfecta. Parte I - Simancas-Escorcia, Víctor Hugo; Natera-Guarapo, Alfredo Enrique; Acosta-de Camargo, María Gabriela (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Amelogenesis imperfecta (AI) refers to a group of genetic alterations of the normal structure of the dental enamel that disturbs its clinical appearance. AI is classified as hypoplastic, hypocalcified, and hypomaturation. These abnormalities may exist in isolation or associated with other systemic conditions in the context of a syndrome. This article is aimed to thoroughly describe the genes involved in non-syndromic AI, the proteins encoded by these genes and their functions according to current scientific evidence. An electronic literature search was carried out from the year 2000 to December of 2017, preselecting 1,573 articles, 63 of which were analyzed and discussed. The results indicated that mutations in 16 genes are responsible for nonsyndromic AI: AMELX, AMBN, ENAM, LAMB3, LAMA3, ACPT, FAM83H, C4ORF26, SLC24A4, ITGB6, AMTN, MMP20, KLK4, WDR72, STIM1, GPR68. Future research with a translational approach will help identify new mutations or genes, contributing to the evolution in the way of classifying, diagnosing and treating the various types of amelogenesis imperfecta.